Compact Invariant Sets for Global Holomorhic Foliations - Fernandez-Perez, A (2017)
We study compact invariant sets for holomorphic foliations on Stein manifold. As application, we show some dynamical properties concerning minimal sets (with singularities) of foliations and real analytic Levi-flat hypersurfaces in projective spaces.